2015
DOI: 10.1103/physrevlett.114.176402
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Spontaneous Time-Reversal Symmetry Breaking on the Honeycomb Lattice

Abstract: Phase transitions involving spontaneous time-reversal symmetry breaking are studied on the honeycomb lattice at finite hole-doping with next-nearest-neighbor repulsion. We derive an exact expression for the mean-field equation of state in closed form, valid at temperatures much less than the Fermi energy. Contrary to standard expectations, we find that thermally induced intraband particle-hole excitations can create and stabilize a uniform metallic phase with broken time-reversal symmetry as the temperature is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…On the other hand, quantum gases with magnetic dipole-dipole interaction (DDI), especially the BECs with DDI, have also drawn much attention both experimentally [35][36][37][38] and theoretically [39][40][41][42][43][44][45][46][47][48] in recent years. Relevant studies on spinor BECs with DDI have shown that the interplay between the short-range spin-exchange interaction and the long-range anisotropic DDI can lead to rich topological defects, spin textures and spin dynamics [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quantum gases with magnetic dipole-dipole interaction (DDI), especially the BECs with DDI, have also drawn much attention both experimentally [35][36][37][38] and theoretically [39][40][41][42][43][44][45][46][47][48] in recent years. Relevant studies on spinor BECs with DDI have shown that the interplay between the short-range spin-exchange interaction and the long-range anisotropic DDI can lead to rich topological defects, spin textures and spin dynamics [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Since the dipole-dipole coupling is strongest between nearest neighbors, and decays as a function of distance between lattice sites to the order 1 |r| 3 , we consider the pairing to be between nearest neighbors [26,[59][60][61]. We describe the superfluid order parameter as Δ i j = V i j c i c j δ j,i+ê λ with λ = x, y.…”
Section: Model and Resultsmentioning
confidence: 99%